Spring-mass behavior and electromyographic activity evolution during a cycle-run test to exhaustion in triathletes - Le Meur, Y.; Dorel, S.; Rabita, G.; Bernard, T.; Brisswalter, J.; Hausswirth, C. (Journal of Electromyography and Kinesiology, 2012)
To evaluate spring-mass (SM) behavior and associated electromyographic (EMG) activity during a run to exhaustion following a cycle exercise in trained triathletes.